Filter Protection of Consumers’ Electrical Installations - M. I. Polouyanov; E. S. Schastnaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper justifies necessity to use current filters of symmetric components, in particular, combined filters of positive and negative phase-sequences for protection of three-phase receivers.Results pertaining to calculation of currents of various phase-sequences for emergency cases with small current are presented in the paper. The paper reveals that protective devices designed on the basis of current filters of symmetric components efficiently improve protection of consumers’ electrical installations and increase their operational safety.